GAMBARAN HASIL TERAPI RADIASI DAN KEMORADIASI PASIEN KANKER SERVIKS DI RSUD ARIFIN ACHMAD PEKANBARU PERIODE 2009-2013 - Fadilla Rizki Putri; Amru Sofian; Dimas Pramita Nugraha (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Cervical cancer is the third most common cancer in women in Indonesia. Many cervical cancer cases were found in an advanced stage, so that they were treated by radiation or chemoradiation. Radiation is divided into external radiation and internal radiation. There is no internal radiation done in Arifin Achmad General Hospital Pekanbaru, so that they only use complete external radiation treatment for 25 times. After the therapy, the patient will do a follow-up treatment of pap smears to assess the cancer cells. This research was conducted in Radiotherapy Installation, Pathology Installation and Medical Records Installation at Arifin Achmad General Hospital Pekanbaru to study and reveal the results of radiation and chemoradiation therapy in cervical cancer patients at Arifin Achmad General Hospital Pekanbaru. The results showed that of 79 patients treated with cervical cancer radiation, only 29 patients did the follow up treatment whilst of 31 patients treated with cervical cancer chemoradiation, only 6 patients did the follow up treatment. Only 2 patients treated by radiation were found to have malignant cells in the pap smear treatment. Meanwhile, in cervical cancer patients treated by chemoradiation, 2 patients were still found malignant cells and 1 patient experienced a recurrence. Once treated with radiation, malignant cells on pap smears are found only in 2 patients, while 27 patients were not found and only 1 patient who experienced a recurrence. After chemoradiation therapy in 6 cervical cancer patients who did the follow up, malignant cells are found in 2 patients and in 4 patients no malignant cells was found, while the other 2 patients experienced recurrence. The conclusion of this study is the incompleteness of the data found in the medical records, low patient adherence to do follow-up treatment after therapy, and the lack of education and information given by the health professionals to patients to do a follow up treatment.Keywords: Cervical cancer, Complete radiation , Chemoradiation, Pap smear